2021
DOI: 10.1002/celc.202100216
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte

Abstract: Anodic zinc oxide (AZO) layers are attracting interdisciplinary research interest. Chemists, physicists and materials scientists are increasingly devoting attention to fundamental and application‐related research on these layers. Research work focuses on the application as semiconductor, corrosion protector, adhesion promoter, abrasion protector, or antibacterial surfaces. The structure and crystallinity essentially determine the properties of the AZO coatings. The type and concentration of the electrolyte, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The quality of the resulting galvanic layers depends on both the electrolyte composition [190][191][192], the applied galvanizing regime [191], and the posttreatment applied. This procedure can be executed through anodization [192][193][194][195][196], similar to the case of aluminum discussed earlier, or by the deposition of Ce-modified hydrotalcites, as proposed by Pham et al [197,198]. In summary, among the most promising approaches for corrosion protection could be achieved by subsequent performance of: (i) galvanization; (ii) galvanic layer anodization; (iii) CeCC layer deposition; (iv) phosphate sealing; and (v) hydrotalcite finishing, combined with (vi) advanced polymer deposition.…”
Section: Application Of Cerium Oxide and Soluble Salts-based Material...mentioning
confidence: 99%
“…The quality of the resulting galvanic layers depends on both the electrolyte composition [190][191][192], the applied galvanizing regime [191], and the posttreatment applied. This procedure can be executed through anodization [192][193][194][195][196], similar to the case of aluminum discussed earlier, or by the deposition of Ce-modified hydrotalcites, as proposed by Pham et al [197,198]. In summary, among the most promising approaches for corrosion protection could be achieved by subsequent performance of: (i) galvanization; (ii) galvanic layer anodization; (iii) CeCC layer deposition; (iv) phosphate sealing; and (v) hydrotalcite finishing, combined with (vi) advanced polymer deposition.…”
Section: Application Of Cerium Oxide and Soluble Salts-based Material...mentioning
confidence: 99%
“…In this context, Giurlani et al [9] underscore the escalating interest in galvanic Zn layers, highlighting their diverse applications in corrosion protection, decorative purposes, microelectronics, automotive, urban planning, aircraft, and spacecraft sectors, among others. Furthermore, Zn layers can be subjected to additional anodization, acquiring further advantageous properties [10,11]. Apart from the application of specific electrical regimes [10,12], the electrolytes used for Zn deposition [13-15] play a crucial role in determining the composition, structure, and resulting properties of the Zn layers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Zn layers can be subjected to additional anodization, acquiring further advantageous properties [10,11]. Apart from the application of specific electrical regimes [10,12], the electrolytes used for Zn deposition [13-15] play a crucial role in determining the composition, structure, and resulting properties of the Zn layers. Furthermore, these coating primers can undergo modifications, such as anodization [7, 8, 16] or additional sealing [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, anodization is an established and efficient method used for the electrochemical formation of oxide layers on aluminum [31 -33], copper [34], zinc [35,36], titanium, [37,38] and other valve metals [39,40]. Indeed, it was recently shown that the combination of formation of cerium conversion coatings with anodization enables the successful formation of combined Al 2 O 3 /CeCC coating primers [41].…”
Section: Introductionmentioning
confidence: 99%